2018
DOI: 10.1111/cen.13716
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in postnatal gonadotrophin levels in infancy reflects diverse maturation of the ovarian and testicular hormone synthesis

Abstract: Ovarian hormone synthesis is immature and incapable of responding to gonadotrophin stimulus before 38-42 PM weeks in PT girls, which may explain their highly elevated FSH and LH levels. The higher InhB levels in boys compared to girls may explain sexual dimorphism in FSH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…21 As expected, AMH, inhibin B and TT levels were higher in boys. 22 In contrast, E2 levels were not different in girls and boys. In their study, Ji et al 23 reported that serum E2 in female infants quickly fell to a minimum level at 1-2 months of postnatal life and sex difference disappeared.…”
Section: Discussionmentioning
confidence: 84%
“…21 As expected, AMH, inhibin B and TT levels were higher in boys. 22 In contrast, E2 levels were not different in girls and boys. In their study, Ji et al 23 reported that serum E2 in female infants quickly fell to a minimum level at 1-2 months of postnatal life and sex difference disappeared.…”
Section: Discussionmentioning
confidence: 84%
“…In boys, LH and FSH levels decrease by 6 months of age, however FSH levels remain elevated up to 3-4 years of life in girls (12, 43,45). A recent study of both full-term and pre-term infants suggests that gonadal feedback mediated by sex steroids, and inhibin B can influence the sexual dimorphism for FSH and LH levels during minipuberty (46).…”
Section: Normal Minipubertymentioning
confidence: 99%
“…The higher FSH levels have been related to ovarian immaturity, with delayed follicular development at ultrasonography and delayed onset of the negative feedback of ovarian hormones on gonadotropins. A recent study (41) showed that the high gonadotrophin levels of preterm girls decrease between 38 and 42 weeks of post-conception age, concurrently with a steep increase of estradiol, even if LH and estradiol are still positively correlated between 4 and 6 months of life. Estradiol in preterm girls increase later than testosterone in preterm boys and its peak is strongly correlated with uterus and breast growth (42).…”
Section: Figures 1 2 Summarize Prenatal and Early Postnatal Changes mentioning
confidence: 99%